Value Pluralism in Legal Ethics - W. Bradley Wendel (Washington University Law Quarterly, 2000)
My claim in this Article is that the foundational normative values of lawyering are substantively plural and, in many cases, incommensurable. By plural I mean that the ends served by the practice of lawyering are fundamentally diverse, and are therefore valued in different ways. Lawyers promote multiple worthwhile goals, including not only preserving individual liberty, speaking truth to power, showing mercy, and resisting oppression, but also enhancing order and stability in opposition to the “ill-considered passions” of democracy, aligning individual action with the public good, and shaping disputes for resolution by particular institutions such as courts and agencies. The claim of incommensurability should not be confused with the familiar argument that in a multicultural, diverse society, the lawyer and client may disagree about justice and the lawyer may face a choice between following her own moral principles or those of her client. Instead, my argument is that the lawyer seeking to act ethically must take account of different value claims that may not be comparable with one another in an impersonally rational, mathematical, or algorithmic manner.
Keywords: Legal ethics; Jurisprudence; Value Pluralism